Education on Environmentally Friendly Farming Systems for Rice Farmers (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Food crop farming is the main support for sustainable human survival. The continuous intensification of the use of chemical inputs in food crop farming, especially rice, has created dependency, negative impacts, and environmental degradation. Environmentally friendly agriculture is an important solution to return to natural agriculture, which is a sustainable agricultural system. This community service activity was carried out in Madallo Hamlet, Tarowang Village, South Galesong District, Takalar Regency, South Sulawesi Province. The aim of this community service activity is to increase understanding and awareness of farmers in managing environmentally friendly food crop farming, especially lowland rice. The method for implementing this service is counseling, using lecture methods, case study visualization, and discussions. The core materials in implementing this activity include (1) optimal use of inorganic fertilizer; (2) control of pests and diseases according to ecological limits; (3) integrated plant management; (4) environmentally friendly farming system; (5) maintaining natural land fertility; and (6) local wisdom technology. The results of this community service activity show that in general farmers are enthusiastic and responsive in understanding and discussing the importance of environmentally friendly agriculture, especially for rice crops. Farmers also feel that their understanding and awareness of the urgency of environmentally friendly agriculture have increased. Increasing understanding of farmers' knowledge of the negative impacts of agriculture that is not environmentally friendly is expected to be an important initiation in awareness to implement environmentally friendly agriculture.